2017
DOI: 10.1007/s12011-017-0944-z
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Deficiency and Oxidative Stress Involved in Valproic Acid Induced Hepatotoxicity: Protection by Zinc and Selenium Supplementation

Abstract: Valproic acid (VPA) is an antiepileptic drug, which its usage is limited due to its hepatotoxicity. The present study was conducted to investigate the efficacy of zinc (Zn) and selenium (Se), necessary trace elements, against VPA-induced hepatotoxicity in Wistar rats. The animals were divided into five groups: control, VPA 200 mg/kg, VPA + Zn (100 mg/kg), VPA + Se (100 mg/kg), and VPA + Zn + Se. The administration of VPA for four consecutive weeks resulted in decrease in serum level of Zn in rats. Also, an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 51 publications
3
16
0
Order By: Relevance
“…Zn and Se were responsible for the regulation and homeostasis of different cytoprotective proteins against diabetes-induced oxidative stress and DNA damage in testes. 27 The present study findings demonstrated that Zn and Se combination treatment has beneficial effects in diabetes-induced germ cell damage. The present study showed that the Zn and Se combination treatment modulated the plasma Zn level and testicular Zn and Se levels during the diabetic condition.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Zn and Se were responsible for the regulation and homeostasis of different cytoprotective proteins against diabetes-induced oxidative stress and DNA damage in testes. 27 The present study findings demonstrated that Zn and Se combination treatment has beneficial effects in diabetes-induced germ cell damage. The present study showed that the Zn and Se combination treatment modulated the plasma Zn level and testicular Zn and Se levels during the diabetic condition.…”
Section: Discussionsupporting
confidence: 66%
“…26 It has been shown that the combination of Zn þ Se showed more protective effects than per se Se in valproic acidinduced hepatotoxicity in Wistar rats. 27 Table 1 summarizes the various reports on the protective effect of Zn and Se in different experimental studies alone as well as in combination. Considering the significance of germ cell damage and the increased incidences of diabetes in humans, the present intervention study was undertaken with the combination treatment of Zn and Se to explore the possible ameliorative effects.…”
Section: Introductionmentioning
confidence: 99%
“…21 Furthermore, the hepatotoxic effects of VPA have been associated with depressed levels of serum zinc and selenium contributing to oxidative damage, as well as histological and biochemical defects in hepatocytes of rats. 22 In another report, VPA treatment reduced the cell viability of HepG2 hepatic cancer cell line and increased the release of ALT and AST from these cells. 23 On the other hand, the cytotoxic effects of VPA have been modulated by genetic variations in Cytochrome P450 2C9 (CYP2C9) and Acyl-CoA Synthetase Medium Chain Family Member 2A (ACSM2A) genes.…”
Section: Discussionmentioning
confidence: 93%
“…VPA-induced hepatotoxicity promotes oxidative stress and elevate the production of ROS (Karaca et al, 2014). Ahangar et al (2017) showed that as a result of VPA application of 200 mg/kg/day for 4 weeks, the level of MDA increased compared to the control group, and lipid peroxidation decreased with Zn and Se supplementation. In this study, MDA level increased in VPA group compared to control, although GLP-2 supplementation partially decreased MDA level, but it was not statistically significant.…”
Section: Discussionmentioning
confidence: 95%